(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article is devoted to the study of the stories of the famous writer of the 20th century (GulamAminov). The article reveals that the writer’s stories “a well-meaning person”, “thirst” are subject to analysis, and in the dramatic development of the events of adib’s works, the skillful use of the molding method in the letter, verse reflects certain aspects of the individuality of Fame, and on the second hand, the validity of realism in his works, the As a result, it was found that the creativity inherent in fame, through its own artistic interpretation, was embodied in the components of the above stories, in the images the contradictions in life not only exerted their influence on the human soul, but also caused its anguish, these images served to illuminate the character and psyche of the hero, revealed the